Oxidative thiocyanation of allylic alcohols: an easy access to allylic thiocyanates with K2S2O8 and NH4SCN. Issue 4 (7th January 2022) - Zhang, Keyuan; Liang, Tianbing; Wang, Yulong; He, Chonglong; Hu, Mingyou; Duan, Xin-Hua; Liu, Le
Abstract : A practical method for the synthesis of allylic thioacyanates from allylic alcohols was disclosed employing K2 S2 O8 as the oxidant and NH4 SCN as the thiocyanate source. Abstract : A practical method for the synthesis of allylic thioacyanates from allylic alcohols was disclosed employing K2 S2 O8 as the oxidant and NH4 SCN as the thiocyanate source. Without introducing a leaving group in advance, a series of disubstituted and monosubstituted allylic thiocyanate compounds were obtained in moderate to good yields. This transition metal-free method features mild reaction conditions, broad substrate scope and operational simplicity. The potential application of this method was demonstrated by some derivatization reactions of the product and mechanistic investigation indicated that a radical process is involved.